RNA editing of 5‐HT2CR impairs insulin secretion of pancreatic beta cells via altered store‐operated calcium entry. Issue 10 (23rd September 2021) - Xie, Ke‐Yun; Chien, Shao‐Ju; Tan, Bertrand Chin‐Ming; Chen, Yun‐Wen
Abstract: Recent studies emphasize the importance of 5‐HT2C receptor (5‐HT2C R) signaling in the regulation of energy homeostasis. The 5‐HT2C R is the only G‐protein‐coupled receptor known to undergo post‐transcriptional adenosine to inosine (A‐to‐I) editing by adenosine deaminase acting on RNA (ADAR). 5‐HT2C R has emerged as an important role in the modulation of pancreatic β cell functions. This study investigated mechanisms behind the effects of palmitic acid (PA) on insulin secretion in different overexpressed 5‐HT2C R edited isoforms in pancreatic MIN6 β cells. Results showed that the expressions of 5HT2C R and ADAR2 were upregulated in the pancreatic islets of mice fed with high‐fat diet (HFD) compared to control mice. PA treatment significantly induced the expressions of 5‐HT2C R and ADAR2 in pancreatic MIN6 β cells. PA treatment significantly induced the editing of 5‐HT2C R in pancreatic MIN6 β cells. There was no significant difference in cell viability between naïve cells and three overexpressed 5‐HT2C R edited isoforms in pancreatic MIN6 β cells. Overexpressed 5‐HT2C R edited isoforms showed reduced glucose‐stimulated insulin secretion (GSIS) compared with green fluorescent protein (GFP) expressed cells. Moreover, 5‐HT2C R edited isoforms displayed reduced endoplasmic reticulum (ER) calcium release and store‐operated calcium entry (SOCE) activation, probably through inhibition of stromal interaction molecule 1 trafficking under PA treatment. Altogether, our results show that PA‐mediated editing of 5‐HT2C R modulates GSIS through alteration of ER calcium release and SOCE activation in pancreatic MIN6 β cells.